Learning statistics using realistic mathematics education: A case of fifth-grade students of elementary school - Widyanthi, Astri; Fatmawilda, Fatmawilda; Putra, Zetra Hainul; Alim, Jesi Alexander (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2023)
This study aims to describe realistic mathematics education (RME) in helping students' understanding of concepts in statistical material about data collection. This research uses descriptive qualitative research methods with a design research approach. The subjects of the study were 29 fifth-grade students of a public school in Pekanbaru, Riau, Indonesia. The results of this study show that RME is applied in learning with the following steps, namely first, providing and explaining contextual problems to be solved by students; second, students solve contextual problems for mathematical models in their own way; third, discuss and compare each problem solving given by students; Fourth, students conclude and summarize the learning concept. From these activities, students can develop knowledge and skills in collecting and presenting data.